2020
DOI: 10.18632/aging.202318
|View full text |Cite
|
Sign up to set email alerts
|

Neuritin-overexpressing transgenic mice demonstrate enhanced neuroregeneration capacity and improved spatial learning and memory recovery after ischemia-reperfusion injury

Abstract: Acute ischemia-reperfusion (IR)-induced brain injury is further exacerbated by a series of slower secondary pathogenic events, including delayed apoptosis due to neurotrophic factor deficiency. Neuritin, a neurotrophic factor regulating nervous system development and plasticity, is a potential therapeutic target for treatment of IR injury. In this study, Neuritin-overexpressing transgenic (Tg) mice were produced by pronuclear injection and offspring with high overexpression used to generate a line with stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…com/article/10.3390/ijms24108565/s1. References [55][56][57][58][59][60][61] are cited in the Supplementary Materials. Informed Consent Statement: Not applicable.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…com/article/10.3390/ijms24108565/s1. References [55][56][57][58][59][60][61] are cited in the Supplementary Materials. Informed Consent Statement: Not applicable.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Results suggest that the cells were viable after electrical stimulation (Figure 4b); which corroborates with prior study results utilizing identical parameters delivered via a wired system. [8,12] Evaluation of gene expression changes after stimulation via quantitative real-time polymerase chain reaction (qRT-PCR) analysis revealed that certain genes implicated in stroke recovery, vascular endothelial growth factor B (VEGFB) and neuritin-1 (NRN1), which are crucial for blood vessel formation and neural regeneration, [22,23] respectively, were upregulated in comparison to unstimulated control cells (Figure 4c). This data supports findings from prior work, [8,11] where a similar effect is demonstrated with the tethered stem cell scaffold system, indicating that this novel wireless powered system can confer analogous results.…”
Section: In Vitro Cellular Characterizationsmentioning
confidence: 99%
“…Numerous mechanisms underly the protective effect of RIC on neurons, and the suppression of apoptosis might be one of them. Neuronal apoptosis is a crucial pathological change in cognitive function associated with acute or chronic cerebral hypoperfusion ( Poh et al, 2020 ; Wan et al, 2020 ), which is characterized by downregulation of anti-apoptotic Bcl-2, upregulation of pro-apoptotic Bax, and activation of caspases ( Wang X. X. et al, 2020 ). Thereby, anti-apoptosis is considered a target for VCI.…”
Section: Role Of Ric In Mitigating Vcimentioning
confidence: 99%